Nilai Pendidikan Karakter “Kerja Keras” Menurut Al-Qur’an (Kajian Tafsir Al-Misbah dan Al-Wasith) - Nahar, Syamsu; Budiman, Budiman; Maya Sari, Dewi (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
This study aims to: 1) Describe the passages in the Qur'an that promote hard labor and character development and how mufassir interprets them. 2) Describe the fundamental guidelines for effective work found in the Qur'an. 3) Examine the meanings of toil in the Qur'an. In this work, interpretive science is combined with the Maudhu'i interpretation method. The Qur'an serves as the study's main source of data, along with the Tafsir Al-Mishbah by M. Quraish Shihab, the Tafsir Al-Azhar by Hamka, the Tafsir Al-Wasith by Wahbah Zuhaili, and other scholarly writings, articles, journals, and other materials with pertinent discussion where necessary. The study's findings reveal that: 1) The Al-Qur'an has numerous verses that call for individuals to reflect, such as Surah Al-Qasas verse 77, Surah An-Najm verses 39–41, Surah Az-Zumar verse 39, Surah At-Taubah verse 105, Surah An-Naba' verse 11, and Surah Al-Jumu'ah verse 10. 2) The fundamental teachings of the Qur'an, which advise Muslims to work hard because work is worship, mercy, a duty, an honor, a calling, an expression of gratitude, art, actualization, and a field of good acts, 3) According to the Qur'an, character education should emphasize values like tenacity, diligence, creativity, discipline, and devotion.